Strengthening anticipatory action through flood forecasting and early warning systems to mitigate flood impacts in Nigeria - Oke, Adebayo; Amarnath, Giriraj; Okem, Andrew; Dembélé, Moctar (CGIAR Initiative on Climate Resilience, 2023)
Flood risks are a major concern in Nigeria, due to their consequences on human life and socioeconomic activities of the people. Floods are induced by high rainfall intensity resulting from climate change. Other factors identified as the drivers of the perennial flooding in Nigeria include, poor drainage systems, poor waste management, unregulated urbanization, weak implementation of planning laws and changes in land use without regard to ecological considerations.